The Interpretation of Philosophical and Religious Values in Gending Sriwijaya Dance as an Instructional Medium for Teaching Local Culture in Formal Education - Naomi Diah Budi Setyaningrum; Hartono; Malarsih; Widodo Brotosejati (Journal for Lesson and Learning Studies, 2025)
The interest of the younger generation in understanding and preserving traditional dance is steadily declining, as school learning remains focused on cognitive aspects and rarely utilizes cultural arts as learning resources. Consequently, the philosophical and religious values embedded in the Gending Sriwijaya dance are not optimally conveyed to students. This study aims to explore and interpret the philosophical and religious values contained in the Gending Sriwijaya dance as a representation of the local cultural identity of the Palembang community in Indonesia. Using an Aesthetics Philosophy approach (phenomenology), this study examines how these values reflect the spiritual and cultural worldview of the local community. A qualitative descriptive method was employed, with data collected through literature review, field observation, and in-depth interviews. The analysis was conducted using a phenomenological approach to uncover the deeper meanings behind the dance movements and accompanying cultural symbols. The findings indicate that the Gending Sriwijaya dance, functioning as a welcoming performance, embodies values of respect and hospitality while employing symbolic properties such as tanggai, tepak, and prindon. Movements such as Siguntang Mahameru, Mudra, Sembah, and Tolak Arus carry profound philosophical meanings. In addition to its religious functions, the dance also plays roles in education, performance, and cultural tourism. These findings suggest that the Gending Sriwijaya dance has significant potential as an instructional medium in teaching local culture within formal education, while also strengthening students’ understanding of the nation’s cultural, philosophical, and religious values.